Technical and economic efficiency of the unconventional propulsion units use for civilian aircraft of various purposes - A. R. Polyakov; O. A. Smolyakov; E. A. Ozdoeva; A. M. Neklyudova; V. S. Zakharchenko; А. N. Varyukhin (Вестник университета)
In order to develop a methodological apparatus for assessing various stages of the life cycle of hybrid/electric propulsion units, the existing approaches to estimating the costs of developing, manufacturing and operating aircraft engines of the traditional propulsion units scheme for determining the cost framework and their further harmonization with the technical and economic boundary conditions of new elements in the hybrid/electric SU scheme are considered. The relevance of solving the problems of assessing the technical and economic efficiency and forecasting the cost of hybrid propulsion units is determined. To solve the tasks, a methodological approach to determining boundary conditions and criteria is proposed. Within the framework of this methodological approach, a preliminary assessment of the cost of the main stages of the life cycle of aircraft engines for various variants of traditional propulsion units was made. Based on the estimates obtained, criteria for the economic efficiency of using a hybrid propulsion unit of various capacities for civil aircraft were formed. A computational and parametric analysis of the cost estimation of variants of aircraft engines included in the propulsion unit of the traditional scheme is presented. The role of accounting and management accounting data in economic and mathematical models is determined, which makes it possible to qualitatively reflect the economic efficiency of the life cycle of aviation products.